Viable super inflation scenario from F(T) modified teleparallel gravity - Keskin, Ali İhsan (EUROPEAN PHYSICAL JOURNAL C, 2018)
Viability of the super inflation scenario is discussed in F(T) modified teleparallel gravity. We calculate the power spectrum of the primordial curvature and tensor perturbations, and we derive two important parameters corresponding to these perturbations, i.e., spectral index parameter n s and scalar-to-tensor ratio r. We observe that the super inflation scenario provides a nearly scale invariant power spectrum of scalar and tensor perturbations in the observational bounds of n(s) and r, according to choosing the proper values interval of the power-term of the scale factor, a similar to t(h).
Keywords: UNIVERSE; FLATNESS; HORIZON